2015
DOI: 10.1016/j.renene.2014.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of Azimuth Tracking Fixed Mirror Solar Concentrator

Abstract: a b s t r a c tThe fixed mirror solar collector (FMSC) fixes reflector and mobiles receiver to collect solar energy. However, this type of concentrator has a low efficiency and short operating duration in practical applications. In this paper, we propose to install the FMSC on an azimuth tracking device (ATFMSC) and the reflectors are arranged by intermission to avoid the shading of neighbor reflector for incidence angle of less than 10 to improve its optical performance. Through the integration of the reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…FMSC is not a proven technology for large scale electric power generation till to date due to its low efficiency. Li et.al [76] developed an Azimuth tracking system which improved optical performance by reducing shading effects of neighbouring reflectors for incident angle of less than 10°. The proposed system was validated by ray tracking results and showed that the design can produce temperature of 400°C with 61% efficiency.…”
Section: Fixed Mirror Solar Concentratormentioning
confidence: 99%
See 1 more Smart Citation
“…FMSC is not a proven technology for large scale electric power generation till to date due to its low efficiency. Li et.al [76] developed an Azimuth tracking system which improved optical performance by reducing shading effects of neighbouring reflectors for incident angle of less than 10°. The proposed system was validated by ray tracking results and showed that the design can produce temperature of 400°C with 61% efficiency.…”
Section: Fixed Mirror Solar Concentratormentioning
confidence: 99%
“…Large solar pond can be deployed for multiple applications such as power generation, thermal energy storage, space or industrial process heating to make the plant economically viable [73,76]. Solar Pond has immense potentiality to be deployed for power generation and energy storage system.…”
Section: Biomass Combustionmentioning
confidence: 99%
“…Renewable energy sources are friendlier to the environment and more sustainable compared to fossil fuels Renewable energy includes several forms such as solar and wind energy [1][2][3][4][5][6]. The sun tracking system in different solar energy applications plays an important role where its benefits over the fixed systems not limited to the power and efficiency gains and increase, but also in the large-scale solar energy applications economic analyses [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The predominant two categories of tracking-single and dual axis tracking-have different features compared to each other. Although the dual-axis tracking is more complicated and has a higher cost, which uses more instruments and equipment [7][8][9][10][11][12][13]. Solar tracking systems can be divided into two main types, namely, active and passive solar tracking systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation